Adult Onset Still’s Disease: A Review on Diagnostic Workup and Treatment Options - Rajesh Gopalarathinam; Eric Orlowsky; Ramesh Kesavalu; Sreeteja Yelaminchili (Case Reports in Rheumatology)
Adult onset Still’s disease (AOSD) is a rare systemic inflammatory disease of unknown etiology and pathogenesis that presents in 5 to 10% of patients as fever of unknown origin (FUO) accompanied by systemic manifestations. We report an interesting case of a 33-year-old African-American male who presented with one-month duration of FUO along with skin rash, sore throat, and arthralgia. After extensive workup, potential differential diagnoses were ruled out and the patient was diagnosed with AOSD based on the Yamaguchi criteria. The case history, incidence, pathogenesis, clinical manifestations, differential diagnoses, diagnostic workup, treatment modalities, and prognosis of AOSD are discussed in this case report.